2012
DOI: 10.1111/j.1471-3802.2012.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dyslexia in higher education: the York adult assessment battery‐revised

Abstract: Although there are a number of standardised measures to assess dyslexia in children, there are comparatively fewer instruments suitable for the assessment of dyslexia in adults. Given the growing number of students entering UK higher education institutions, there is a need to develop reliable tools for assessing the additional needs of those with dyslexia and related difficulties. This study reports data from a revised version of the York Adult Assessment: An Assessment Battery for Dyslexia Screening in Higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 27 publications
(34 reference statements)
2
60
0
1
Order By: Relevance
“…The importance of reading assessment in adults is amply recognized (Elbro et al, ; Johnson et al, ; Lewandowski et al, ; Miller‐Shaul, ; Nergård‐Nilssen & Hulme, ; Re et al, ; Reid et al, ; Santana et al, ; Shaywitz et al, ; Simmons & Singleton, ; Stevens & Price, ; Warmington et al, ; Wilson & Lesaux, ). However, no norm‐referenced test was hitherto available for assessing reading comprehension in Portuguese adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of reading assessment in adults is amply recognized (Elbro et al, ; Johnson et al, ; Lewandowski et al, ; Miller‐Shaul, ; Nergård‐Nilssen & Hulme, ; Re et al, ; Reid et al, ; Santana et al, ; Shaywitz et al, ; Simmons & Singleton, ; Stevens & Price, ; Warmington et al, ; Wilson & Lesaux, ). However, no norm‐referenced test was hitherto available for assessing reading comprehension in Portuguese adults.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, little research has been devoted to standardized reading tests for adults (Lewandowski et al, ; Miller‐Shaul, ; Nergård‐Nilssen & Hulme, ; Re et al, ; Stevens & Price, ; with some exceptions, see, e.g. Warmington et al, ). Indeed, at least four main reasons argue for the need of such tests with good psychometric properties.…”
mentioning
confidence: 99%
“…It is a longlasting deficit that persists into adulthood (Gabrieli, 2009). It has been reported that approximately 3.2% of the dyslexics in the UK manage to undertake university studies despite having dyslexia (Warmington, Stothard, & Snowling, 2013). University students with dyslexia are an ideal population to investigate how the reading network had adapted, both spatially and temporally, to compensate for reading deficits of adults with dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Letter cancellation test (LCT): was used to assess unilateral neglect (12) 3. Reading ability screening test (RAST): it is first subtest of the York Adult Assessment Battery-Revised with components of reading comprehension, accuracy, time, and rate) [15] Protocol All 10 subjects underwent comprehensive occupational therapy program for 1 hour, thrice a week for 6 weeks comprising of visual scanning, visual discrimination, and visual spatial training with reading-related tasks. Left hand somatosensory stimulation was incorporated with tactile stimulation using textures, identification of 3-D alphabets, and graphesthesia (writing single numbers or letters on dorsum of left hand) [1,11].…”
Section: Outcome Measuresmentioning
confidence: 99%